Focal TLR4 activation mediates disturbed flow-induced endothelial inflammation. Issue 1 (20th February 2019) - Qu, Dan; Wang, Li; Huo, Mingyu; Song, Wencong; Lau, Chi-Wai; Xu, Jian; Xu, Aimin; Yao, Xiaoqiang; Chiu, Jeng-Jiann; Tian, Xiao Yu; Huang, Yu
Abstract: Aims: Disturbed blood flow at arterial branches and curvatures modulates endothelial function and predisposes the region to endothelial inflammation and subsequent development of atherosclerotic lesions. Activation of the endothelial Toll-like receptors (TLRs), in particular TLR4, contributes to vascular inflammation. Therefore, we investigate whether TLR4 can sense disturbed flow (DF) to mediate the subsequent endothelial inflammation. Methods and results: En face staining of endothelium revealed that TLR4 expression, activation, and its downstream inflammatory markers were elevated in mouse aortic arch compared with thoracic aorta, which were absent in Tlr4 mut mice. Similar results were observed in the partial carotid ligation model where TLR4 signalling was activated in response to ligation-induced flow disturbance in mouse carotid arteries, and such effect was attenuated in Tlr4 mut mice. DF in vitro increased TLR4 expression and activation in human endothelial cells (ECs) and promoted monocyte-EC adhesion, which were inhibited in TLR4-knockdown ECs. Among endogenous TLR4 ligands examined as candidate mediators of DF-induced TLR4 activation, fibronectin containing the extra domain A (FN-EDA) expressed by ECs was increased by DF and was revealed to directly interact with and activate TLR4. Conclusion: Our findings demonstrate the indispensable role of TLR4 in DF-induced endothelial inflammation and pinpoint FN-EDA as the endogenous TLR4 activator in this scenario. This novel mechanism of vascular inflammation under DF condition may serve as a critical initiating step in atherogenesis.